Role Playing Strategy to Develop Self-Confidence Character in Early Childhood: A Case Study at TK ABA 01 Kota Batu - Chosiah, Chosiah; Akbar, Sa’dun; Aisyah, Eny Nur; Arifin, Imron (Electronic Journal of Education, Social Economics and Technology, 2025)
This research is motivated by the lack of self-confidence character in early childhood, which has a significant impact on their future development. The aim of this study is to explore how roleplaying games can help foster self-confidence in young children through engaging and enjoyable learning activities. The focus of the research includes: (1) the implementation of roleplaying games at TK ABA 01 Kota Batu, (2) the process of developing self-confidence character in this setting, and (3) the impact of roleplaying games on building self-confidence. This research uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which consists of data collection, condensation, display, and conclusion drawing. The validity of the data was ensured through triangulation of sources, data, and time. The findings indicate that consistent application of roleplaying games at TK ABA 01 Kota Batu effectively enhances self-confidence in children. Through these structured and regular activities, children showed improvements in communication skills, empathy, and courage to face challenges. Roleplaying games also contributed to the development of other positive character traits such as cooperation, independence, and responsibility. Therefore, integrating roleplaying games into early childhood education is recommended as an innovative and effective strategy for holistic character development. This method can serve as a valuable approach for supporting the formation of self-confidence and other essential character values in early childhood educational institutions.